KATTALAR TA’LIMI PEDAGOGIK MUAMMO SIFATIDA - Davletova, A.A. (SCIENCE and SOCIETY, 2025)
This article presents the classification of age periods for adults and scholars’ views on the concept of magnitude. Thus, most scientists focus on the socio-psychological characteristics of an adult, which distinguish them from minors (children and adolescents).
Keywords: adult; mature; UNESCO; education; formal education; informal education; andragogical model